Effect of atomic size mismatch and chemical complexity on the local lattice distortion of BCC solid solution alloys. (December 2022) - Zhang, F.X.; Song, Hong-Quan
Abstract: The effects of atomic size mismatch and chemical complexity on the local lattice distortion of solid-solution alloys VNbTa, TiVNbMo, TiVNbMoTa and TiVNbMoTaWRe with body-centered cubic (BCC) structure are quantitatively studied with time-of-flight neutron total scattering, extended X-ray absorption fine structure (EXAFS) measurements and first principles calculations. Neutron atomic pair distribution function (PDF) measurements found that the local lattice distortion in the ternary solid-solution alloy VNbTa is 1.1 %, obviously larger than that of the most complicated solid-solution alloy (0.27% for TiVNbMoTaWRe). Our results suggested that atomic size mismatch in high entropy alloys is more critical to the local lattice distortion than chemical complexity. Both EXAFS analysis and theoretical calculations indicate that there is a maximum of ∼4 % difference between the bonding length of different atomic pairs in VNbTa. Graphical Abstract: ga1 Highlights: Combination of total scattering, EXAFS and first-principles calculation can quantitatively study the local structural details of high entropy alloys. Local lattice distortion is more sensitive to atomic size mismatch than the chemical complexity in high entropy alloys. The interatomic distance of the same pairs varies slightly in different solid solution alloys.